Influence of Work-Life Balance Practices on Health-Related Outcomes and Exit Intentions: A Study among Employees of the Nigerian Federal Polytechnic - Makinde, Wasiu Abiodun; Idowu, Michael Tanpinnu (The Indonesian Institute of Science and Technology Research, 2025)
A key component of employee job satisfaction, performance, health-related outcomes, and exit intentions is the ability to successfully strike a balance between professional obligations and personal commitment and well-being. This study looked at how work-life balance practices affected employees' health-related outcomes and plans to leave the Federal Polytechnic in Nigeria. By administering a questionnaire to a sample size of 274 people, which was determined by using Krejcie and Morgan sampling procedures and chosen through a stratified sampling approach, the study utilised a quantitative way of survey research design. Regression analysis and ANOVA, two inferential statistics, were used to evaluate the obtained data. The analysis of how work-life balance practices affect health-related outcomes among Federal Polytechnic employees in Ilaro, Ogun State, found that work-life balance practices account for approximately 37% of the variation in health-related outcomes among Federal Polytechnic employees in Ilaro, Ogun State. Additionally, it was shown that work-life balance practices, including flexible work schedules, leadership support, organisational culture, and generous leave policies, were responsible for almost 54% of the differences in exit intentions among Federal Polytechnic, Ilaro Ogun State employees. The study found that while work-life balance practices like flexible work schedules and generous leave policies differ significantly between teaching and non-teaching staff, health-related outcomes and exit intentions resulting from these practices do not differ significantly between the two groups. According to the study's findings, work-life balance policies have an impact on employees' health-related outcomes and plans to leave the Federal Polytechnic in Nigeria.